Peace through International Law
IX, 197 p.
Keywords: Georg Nolte Excellencies, dear Colleagues, Ladies and Gentlemen, I welcome you to our colloquium on the occasion of the sixtieth an- versary of the International Law Commission. The Ludwig Maximilians University of Munich and the Humboldt University of Berlin are happy that you have followed our invitation. We are particularly proud that a majority of the members of the Int- national Law Commission have accepted our invitation. The presence of one former member of the Commission deserves special mention: Bruno Simma is now not only a Judge at the International Court of J- tice but also, if I may say so, the “local hero”, having held the wond- ful Chair for International Law at the University of Munich for more than thirty years. He is still living in Munich when he is not in The Hague. We are glad that participants have come from nearby, from neighbouring regions and countries, as well as from countries as far away as Brazil and China. I am personally very content that our group represents a fine mixture of experienced international lawyers and younger colleagues and students. This composition gives us the opp- tunity for fruitful exchanges, and for the ILC to reach out and to - ceive feedback. The International Law Commission needs no introduction. Like a few happy persons, at age sixty it can look back onto a largely successful - reer.